x → π / 2 lim ( π − 2 x ) 2 1 + cos 2 x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Substituting t = 2 π − x we have lim t → 0 4 t 2 1 + cos ( π − 2 t ) = lim t → 0 4 t 2 1 − cos ( 2 t ) = lim t → 0 4 t 2 2 sin 2 ( t ) = 0 . 5
Due to our familiarity with Maclaurin series, it is often helpful to use a change of variables so that we're evaluating the limit at 0.
Applying Taylor series of cos x around x = π , then cos x = − 1 + 2 ! ( x − π ) 2 − . . . . x → 2 π lim ( π − 2 x ) 2 1 + cos 2 x = x → 2 π lim ( π − 2 x ) 2 2 ! ( 2 x − π ) 2 = 0 . 5
Problem Loading...
Note Loading...
Set Loading...
lim x → 2 π ( π − 2 x ) 2 1 + cos 2 x S i n c e i t i s a 0 0 f o r m , s o w e n e e d t o s i m p l i f y i t . ⇒ lim x → 2 π ( π − 2 x ) 2 1 − cos ( π − 2 x ) ⇒ lim x → 2 π ( π − 2 x ) 2 1 − ( 1 − 2 sin 2 2 ( π − 2 x ) ) { U s i n g cos x = 1 − 2 sin 2 2 x ) O p e n i n g t h e b r a c k e t s , ⇒ lim x → 2 π ( π − 2 x ) 2 2 sin 2 2 ( π − 2 x ) ⇒ lim x → 2 π 2 ( π − 2 x ) 2 sin ( 2 ( π − 2 x ) ) 2 M u l t i p l y i n g a n d d i v i d i n g 2 i n t h e d e n o m i n a t o r , ⇒ lim x → 2 π ( 2 ( π − 2 x ) ) 2 2 sin ( 2 ( π − 2 x ) ) 2 S e p a r a t i n g t e r m s , ⇒ lim x → 2 π ( 2 ( π − 2 x ) ) 2 sin ( 2 ( π − 2 x ) ) 2 × lim x → 2 π 2 1 B u t i f x → 2 π , S o , 2 x − π → 0 , O r , π − 2 x → 0 C h a n g i n g l i m i t s ⇒ lim π − 2 x → 0 ( 2 ( π − 2 x ) ) 2 sin ( 2 ( π − 2 x ) ) 2 × lim x → 2 π 2 1 B u t lim x → 0 x sin x = 1 , S o , f i r s t t e r m = 1 T h e r e f o r e , ⇒ lim x → 2 π 2 1 = 2 1 = 0 . 5